A Novel Method to Realize Optical Correlation Recognition Based on Neural Network - Ping Xu; Tuo Yang; Kai Liang; Xiongchao Li; Siwei Long; Haixuan Huang (IEEE Photonics Journal)
A neural network model is constructed according to 4F optical correlator. New optical filter is obtained by training the neural network. For recognition of distortion targets, the correlation peaks from correlator applying new filter are averagely increased up to 306.7% than applying the OTSDF filter, and correlation peaks are higher, sharper and easier to be distinguished, which indicates optical correlator with new filter have better performance in distortion invariant recognition.